2016
DOI: 10.1111/1753-0407.12354
|View full text |Cite
|
Sign up to set email alerts
|

Effect of renal function on serum concentration of 1,5‐anhydroglucitol in type 2 diabetic patients in chronic kidney disease stages I–III: A comparative study with HbA1c and glycated albumin

Abstract: In clinical practice, age and renal function must be taken into consideration when interpreting 1,5-AG levels, even in the absence of advanced renal impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…Christoph Hasslacher et al found that there was a negative correlation between 1,5-AG and renal function which could be due to an age-related change in the glucose threshold. Consequently they concluded that in clinical practice, age and renal function must be taken into consideration when interpreting 1,5-AG levels, even in the absence of advanced renal impairment [2].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Christoph Hasslacher et al found that there was a negative correlation between 1,5-AG and renal function which could be due to an age-related change in the glucose threshold. Consequently they concluded that in clinical practice, age and renal function must be taken into consideration when interpreting 1,5-AG levels, even in the absence of advanced renal impairment [2].…”
Section: Resultsmentioning
confidence: 99%
“…Won Jun Kim [1] conducted a cross-sectional study in 2012 and found that 1,5-AG levels were influenced by advanced renal impairment but not mild or moderate renal dysfunction. Nevertheless, Christoph Hasslacher et al [2] hold the opinion that In clinical practice, renal function must be taken into consideration when interpreting 1,5-AG levels, even in patients with earlier chronic kidney disease (CKD) stages. What's more, the sample sizes of these study were small.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interpretation of 1,5-AG variation among adults without diabetes is unclear. It is thought that some of the differences among individuals may be accounted for by differences in renal reabsorption of 1,5-AG [21]. It is also possible that 1,5-AG varies as a result of factors that affect food digestion (for example, microbiota) [12] or nutrient absorption [13].…”
Section: Discussionmentioning
confidence: 99%
“…eGFR was calculated using the MDRD (Modification of Diet in Renal Disease) formula. eGFR ≥ 120 mlsml/min/1.73m 2 was considered to be consistent with hyperfiltration as in previous studies [23][24][25] .…”
Section: Methodsmentioning
confidence: 77%